Prioritizing Pharmaceutical Activities: A Simulation by Pharmacy Residents. (August 2013) - Renet, Sophie; Tanguay, Cynthia; Hall, Kevin; Bussières, Jean-François
Objectives: The primary objective was to examine the consistency of prioritization decisions made by pharmacy residents in a simulated environment where the available resources are constrained. Secondary objectives were to rank the factors that influenced their prioritization and to compare the residents' results with those of Canadian pharmacy leaders. Methods: We have developed a prioritization exercise that aims at evaluating how pharmaceutical activities are prioritized. The simulation was conducted with hospital pharmacy residents in 2 Quebec universities in 2011. Results: Residents covered a similar number of activities in the prioritization simulation (mean 27 of 32). Teams tended to favor a broad range of services delivered less comprehensively. Participants ranked "perception of the favorable impact of the activity on health outcomes" higher than "conclusive evidence available to support the decisions." The relative weight attributed per domain was similar between pharmacy residents and pharmacy leaders, but their ranking of factors that influenced their decisions was different. Conclusions: Pharmacy residents opted to provide a wide range of services, but at a low level of comprehensiveness. The high variation between each team's coverage per activity in this simulation supports the observation that pharmacy residents do not agree on a core set of pharmaceutical activities that should be prioritized.